Characterizing the Asymmetric Dependence Premium. (28th June 2016) - Alcock, Jamie; Hatherley, Anthony
Abstract: We examine the price of asymmetric dependence (AD) in the cross section of US equities. Using a β -invariant AD metric, we demonstrate that the return premium for AD is approximately 47% of the premium for β . The premium for lower-tail AD is equivalent to 26% of the market risk premium and has been relatively constant through time. The discount associated with upper-tail AD is 29% of the market risk premium and has been increasing markedly in recent years. Our findings have substantial implications for the cost of capital, investor expectations, portfolio management, and performance assessment.